Capitalized Amenity Value of Native Vegetation in a Multifunctional Rural Landscape. (1st July 2014) - Polyakov, Maksym; Pannell, David J.; Pandit, Ram; Tapsuwan, Sorada; Park, Geoff
Abstract: In many parts of the world, natural vegetation has been cleared to allow agricultural production. To ensure a long‐term flow of ecosystem services without compromising agricultural activities, restoring the environment requires a balance between public and private benefits and costs. Information about private benefits generated by environmental assets can be utilized to identify conservation opportunities on private lands, evaluate environmental projects, and design effective policy instruments. We use a spatio‐temporal hedonic model to estimate the private benefits of native vegetation on rural properties in the state of Victoria, Australia. Specifically, we estimate the marginal value of native vegetation on private land and examine how it varies with the extent of vegetation on a property and across a range of property types and sizes. Private benefits of native vegetation are greater per unit area on small and medium‐sized properties and smaller on large production‐oriented farms. Native vegetation exhibits diminishing marginal benefits as its proportion of a property increases. The current extent of native vegetation cover is lower than the extent that would maximize the amenity value to many landowners. There is scope for improved targeting of investment in the study region by incorporating private benefits of environmental projects into environmental planning processes. Landowners with high marginal private benefits from revegetation would be more willing to participate in a revegetation program. Targeting these landowners would likely provide higher value for money because such projects could be implemented at lower public cost.